(untitled) (Tanzania Medical Journal, 2010)
Background: Suppression of viral replication is the goal of antiretroviral therapy. It is one of the most important factors influencing long-term prognosis of HIV infection. Non-adherence increases the risk of viral mutations which can result in crossresistance and thus the risk for therapy failure. Objectives: To determine the magnitude of intentional nonadherence to antiretroviral therapy among patients receiving antiretroviral therapy comprised of two nucleoside reverse transcriptase inhibitors and one non-nucleoside reverse transcriptase inhibitor at the HIV care and treatment clinic (CTC) of Muhimbili National Hospital (MNH) in Dar es Salaam, Tanzania. Method: A total of 250 patients were recruited between July 2007 and January 2008 at the HIV CTC of MNH. A structured questionnaire was used for interviewing the patients in order to assess intentional non-adherence through recall, as well as the presence of solicited antiretroviral drugs (ARVs) related side effects during the past 3, 7 and 30 days respectively, since ARV initiation. In addition, clinical (weight changes and incident opportunistic illnesses) as well as immunological (CD4 count) progress in the past 2 years was ascertained through review of patients’ clinical documents. Results: About half (45.6%) of the patients reported to have experienced the side effects associated with ARVs. Most patients (70.1%) experienced peripheral neuropathy. Other side effectsreported included; skin itching/rashes (19.6%), breast enlargement (10.3%), abdominal pain (7.5%), dizziness (5.6%), lipodystrophy (4.7%), vomiting (3.7%), poor vision (2.8%), nausea (1.9%), and headache (1.9%). A total of 18 (7.2 %) patients reported to have ever missed taking their medications. Four patients (1.6%) reported to have skipped their medication in the past 3 days; two (0.8%) in the past 7 days; and twelve (4.8%) in the past 30 days. Only 3 (1.2%) patients admitted to have intentionally skipped their doses due to the side effects they experienced while taking ARVs. The median CD4 count and mean body weight increased from 206 cells/?L and 62 kg to 311 cells/ ?L and 65 kg, respectively, during a period of previous 24 months. Conclusion: ARV related side effects were common among patients attending the MNH CTC, but these did not result into significant intentional non-adherence. It is however recommended that a more comprehensive study involving a larger number of patients at different ART providing sites in the country be conducted so as to make a more comprehensive conclusion on this subject. Studies involving self-reported adherence and plasma ARVs concentration measurement area are also necessary in order to make a good correlation of adherence self-reporting and the actual amount of thedrug in the blood.Key words: Intentional non-adherence, ARVs, CD4, Weight change, HIV, Antiretroviral therapy